Profiling secondary metabolites and antioxidant activity of tea mistletoe leaves (Scurrula artopurpurea (Bl.) Danser) in Nglinggo, Kulon Progo, Yogyakarta - Dwi Aditiyarini; Ratih Restiani; Evieyana Evieyana (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.